O problema da mediação imperfeita em Paul Ricoeur - Möbbs, Adriane da Silva Machado (2015)
It is a study of the imperfect mediation in Paul Ricoeur. We hold the view that the ricoeurian thought is articulated based on the notion of imperfect mediation, partial and finite, especially in distinction to the mediation of Hegelian sense is defined in absolute terms. Sustaining this thesis implies on the one hand, to rebuild some internal aspects to the work of Ricoeur, notably that qualify as the three Hegelian temptations, namely: the absolute temptation in the Spirit, in history and in the state. Otherwise, implies examine some theses that prescribe solutions contrary to ours. One is the thesis that defends the unity of Ricoeur's work based on the symbol of paradigms, text and translation; the other is defending the unity of his work around the symbol. In contrast, we understand that symbol, text and translation are but different ways of renouncing all forms of full mediation. In addition, the results we seek to ensure that the imperfect, open and fragmentary mediation remains an uninterrupted dialectic that articulates the self with the other, the identity with otherness.